2019
DOI: 10.1038/s41467-019-10943-1
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: The gut microbiota in infants of obese mothers increases inflammation and susceptibility to NAFLD

Abstract: In addition, the following was added to the Author contributions: 'B.Y. and N.F.K. helped to design the clinical study and participated in the sample collection during the infant visits.' This has been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Soderborg et al colonized germ-free mice with stool derived from 2-week-old infants born to either obese or normal weight mothers (human). 99 100 They showed that the microbiome of infants born to mothers with obesity led to liver reminiscent of steatohepatitis, with increased expression of hepatic genes involved in endoplasmic reticulum stress and innate immunity activation. Importantly, when these offspring were exposed to a Western-style diet, they had increased adiposity and accelerated development of hepatic steatosis and injury.…”
Section: Early Life Risk Factors Of Pediatric Masldmentioning
confidence: 99%
“…Soderborg et al colonized germ-free mice with stool derived from 2-week-old infants born to either obese or normal weight mothers (human). 99 100 They showed that the microbiome of infants born to mothers with obesity led to liver reminiscent of steatohepatitis, with increased expression of hepatic genes involved in endoplasmic reticulum stress and innate immunity activation. Importantly, when these offspring were exposed to a Western-style diet, they had increased adiposity and accelerated development of hepatic steatosis and injury.…”
Section: Early Life Risk Factors Of Pediatric Masldmentioning
confidence: 99%
“…studies, emerging translational data have provided initial insights into the pathogenesis of this condition (12)(13)(14)(15). Despite such key advances in the field, the natural history of the liver disease detected in utero and during the neonatal life is not defined.…”
Section: Translation Impactmentioning
confidence: 99%
“…Similar results were shown in a smaller study by Brumbaugh et al (11). Beyond these observational studies, emerging translational data have provided initial insights into the pathogenesis of this condition (12–15).…”
Section: Introductionmentioning
confidence: 99%